Life Style as Consumer Satisfaction in the Maqāṣid of Islamic Economics - Musfiqoh, Siti (El-Qist: Journal of Islamic Economics and Business (JIEB), 2023)
This study investigates lifestyle as a dimension of consumer satisfaction within the framework of Maqāṣid al-Sharī‘ah in Islamic economics. Using a literature-based analytical approach, the paper critiques conventional economic assumptions of utility and consumer rationality by contrasting them with Islamic normative principles on consumption. It explores how modern lifestyle choices—often shaped by capitalist cultural industries and social expectations—can lead to excessive consumption (isrāf and tabdhīr), diverging from the ethical and spiritual goals of Islamic economic behavior. The analysis emphasizes that true consumer satisfaction in Islam must align with the prioritization of needs (ḍarūriyyāt, ḥājiyyāt, taḥsīniyyāt) rather than desires, promoting holistic well-being across material and spiritual dimensions. This study contributes to global Islamic economics scholarship by offering a normative framework that integrates consumer ethics, spiritual utility, and the maqāṣid-based prioritization of needs. It provides a theoretical alternative to Western-centric models of consumer behavior and introduces Islamic lifestyle moderation as a metric of satisfaction that transcends material utility. Future international research may empirically test the proposed maqāṣid-based satisfaction framework across Muslim societies, explore its implications for ethical consumerism, and develop indices that measure consumption aligned with Islamic values.